THE IBADHIYAH SECT: ITS HISTORY AND THOUGHTS IN POLITICS,THEOLOGY,AND FIQH - Zamzami, Zamzami; Erniwati, Erniwati (Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study is to illustrate that the thinking or concept of teachings adopted and applied Ibadhiyah, one of the sects of the Khawarij sect, is moderate. So that his teachings and followers still exist today in some Muslim countries. They have a high attitude of tolerance towards fellow Muslims of different sects and sects. On the other hand, the sects in the sphere of the other Kharijites which are extreme in thought and action are extinct, no longer have followers. At first, the Khawarij follower’s are Ckhalif ‘Ali bin Abi Thalib group. End then, they go out from ‘Ali group, becauce they weren’t except this reconcillied (tahkim) in Shiffin war between Khalif Ali and Guvernor Mu’awiyah bin Abi Syufyan 37H/657 M. They were against Chalif ‘Ali and Mu’awiyah, and emigrate to a village is colled “Harura”. In this village they were created self-government led by ‘Abdullah ibn Wahhab al-Hasibi. They were againt ‘Ali, Mu’awiyah, and some ckhalif after them. Then Khawarij Follower’s were spilit into several sects. The biggest sect’s: Muhakkimah, Azariqah, Najdah, Ajaridah, Syufriyah, and Ibadhiyah. Such of sect slip up to several sub-setc until twenty. All sects were extinct, except Ibadhiyah. Becauce they were smothered by legitimate Government. They have extreme thought. They carried out takfir and were a sourse of insurrection against the Goverment for centuries. The Ibadhiyah sect were moderate in thought and action. The Ibadhiyah sect exist until now in Sultanate of Oman. It’s majority and state sect in Oman. It spread in Nort Africa (Aljazair, Tunisia, and Libia) and East Africa. Follower Ibadhiyah sect there in in Yemen and Madagascar. Keywords: Ibadhiyah, History, Thought.